2019
DOI: 10.1002/chem.201900617
|View full text |Cite
|
Sign up to set email alerts
|

Role of Water in the Reaction Mechanism and endo/exo Selectivity of 1,3‐Dipolar Cycloadditions Elucidated by Quantum Chemistry and Machine Learning

Abstract: Asymmetric 1,3-dipolar cycloadditionso fa zomethine ylides with activated olefins are among the mosti mportant and versatile methods fort he synthesis of enantioenrichedp yrroline and pyrrolidine derivatives. Despite both theoretical and practical importance, the role of water molecules in the reactivity and endo/exo selectivity remains unclear.T oe xplore how water accelerates the reactions and improves the endo/exo selectivity of the cycloadditionso f 1,3-dipole phthalazinium-2-dicyanomethanide (1)a nd two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 143 publications
0
6
0
Order By: Relevance
“…A recent computational study by Yang and co-workers investigated the role of explicit water molecules on 1,3-cycloaddition reactions using DFT-quality neural network potentials and compared to experimental data. They concluded that even in the most extreme cases considered, aqueous cycloaddition reactions tended to retain a (quasi-)concerted mechanism and most qualitative solvation trends could already be successfully recovered through implicit modelling 34 . Our own benchmarking results also corroborate the adequacy of implicit solvent modelling to recover experimental trends (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…A recent computational study by Yang and co-workers investigated the role of explicit water molecules on 1,3-cycloaddition reactions using DFT-quality neural network potentials and compared to experimental data. They concluded that even in the most extreme cases considered, aqueous cycloaddition reactions tended to retain a (quasi-)concerted mechanism and most qualitative solvation trends could already be successfully recovered through implicit modelling 34 . Our own benchmarking results also corroborate the adequacy of implicit solvent modelling to recover experimental trends (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to this, water has also been shown to improve the reaction rate and promote the endo isomers formation [39,40]. It is thought that the presence of water stabilises the carbonyl group, which reduces the energy barrier for the forward reaction [39].…”
Section: Potential Of the Diels-alder Reaction In Biomedical Applicat...mentioning
confidence: 99%
“…[25][26][27][28] However, the application of MLPs to study chemical processes in solution remains underexplored. The few reported examples include urea decomposition in water, 29 1,3-dipolar cycloadditions in water, 30 and reactions in alkali carbonate-hydroxide electrolytes, 31 with the NNPs being the state-of-the-art approach requiring thousands of AIMD configurations.…”
Section: Introductionmentioning
confidence: 99%
“…Other models only provide a point prediction for a given structure and are thus unable to utilise this metric. 41 Another approach widely used in NNPs, 30,[42][43][44] although not limited to, is query-by-committee, where uncertainty is quantified through the variance of predicted energies or forces among an ensemble of MLPs, referred to as committees. In the case of NNs, multiple potentials are trained with the same architecture but with different initial parameters.…”
Section: Introductionmentioning
confidence: 99%